The UK Cranioplasty Study and Development of the UK Cranial Reconstruction Registry. (16th November 2020) - Fountain, Daniel; Whiting, Gemma; Mee, Harry; Edlmann, Ellie; Joannides, Alexis; Piper, Rory; Turner, Carole L; Kolias, Angelos G; Hutchinson, Peter J
Abstract: INTRODUCTION: Many questions remain without robust evidence in performing cranioplasty operations, including the timing following craniectomy and material. METHODS: Patients undergoing cranioplasty insertion, revision, removal and re-insertion between 1 st June 2019 and 30 th November 2019 in any neurosurgical unit in the UK and Ireland were included. Data collected includes basic demographic data, craniectomy date and indication, cranioplasty material and timing, and 30-day outcome. RESULTS: A total of 348 operations across twenty-five neurosurgical units in the United Kingdom and Ireland were submitted, including 285 new insertions. Of new insertions, the most common indications for craniectomy were acute subdural haematoma (n = 76, 27%), cerebral infarct (n = 42, 15%), and aneurysmal subarachnoid haemorrhage (n = 24, 8%). The most common material was titanium (n = 176, 62%). Median time to cranioplasty was 275 (IQR 166–543) days, with 35 new insertions (14%) within 90 days. In 30-day follow-up, there were 16 readmissions, with 11 patients sustaining a wound infection within 30 days (4%). There were 63 cranioplasty revisions and removals, the most common reason being infection (n = 34, 54%) and skin breakdown (n = 15, 24%). A steering committee has been established to plan the continuation of the UK cranioplasty study as an ongoing registry. CONCLUSION: The UK cranioplasty study is the largest prospective study of cranioplasty and shows promise laying the foundations for a robust registry while providing important insights for outstanding research questions for clinicians performing this procedure.